Point-of-Care Tomosynthesis Imaging of the Wrist - Inscoe, Christina R (Mil Med, 2021)
INTRODUCTION: Musculoskeletal injury to extremities is a common issue for both stateside and deployed military personnel, as well as the general public. Superposition of anatomy can make diagnosis difficult using standard clinical techniques. There is a need for increased diagnostic accuracy at the point-of-care for military personnel in both training and operational environments, as well as assessment during follow-up treatment to optimize care and expedite return to service. Orthopedic tomosynthesis is rapidly emerging as an alternative to digital radiography (DR), exhibiting an increase in sensitivity for some clinical tasks, including diagnosis and follow-up of fracture and arthritis. Commercially available digital tomosynthesis systems are large complex devices. A compact device for extremity tomosynthesis (TomoE) was previously demonstrated using carbon nanotube X-ray source array technology. The purpose of this study was to prepare and evaluate the prototype device for an Institutional Review Board-approved patient wrist imaging study and provide initial patient imaging results. MATERIALS AND METHODS: A benchtop device was constructed using a carbon nanotube X-ray source array and a flat panel digital detector. Twenty-one X-ray projection images of cadaveric specimens and human subjects were acquired at incident angles from −20 to +20 degrees in various clinical orientations, with entrance dose calibrated to commercial digital tomosynthesis wrist scans. The projection images were processed with an iterative reconstruction algorithm in 1 mm slices. Reconstruction slice images were evaluated by a radiologist for feature conspicuity and diagnostic accuracy. RESULTS: The TomoE image quality was found to provide more diagnostic information than DR, with reconstruction slices exhibiting delineation of joint space, visual conspicuity of trabecular bone, bone erosions, fractures, and clear depiction of normal anatomical features. The scan time was 15 seconds and the skin entrance dose was verified to be 0.2 mGy. CONCLUSIONS: The TomoE device image quality has been evaluated using cadaveric specimens. Dose was calibrated for a patient imaging study. Initial patient images depict a high level of anatomical detail and an increase in diagnostic value compared to DR.